Urbanization and the excess mortgage risk – an optimal mortgage model - Hongxia Zhang; Heeho Kim (Humanities & Social Sciences Communications)
Abstract This study investigates the optimal mortgage level and examines the impact of urbanization on the risk of excessive mortgage loan in China’s housing markets. We propose a new model to theoretically derive and measure both the optimal mortgage level and the degree of urbanization across different regions of China. The paper tests two hypotheses: first, whether urbanization directly increases the risk of excess mortgages, and second, whether urbanization indirectly contributes to this risk through its effect on housing prices. Using a fixed-effects model for panel data analysis, the generalized method of moments (GMM), and monthly data from 25 regional provinces in China spanning from 2007 to 2019, our results provide strong evidence in support of these hypotheses. The impact of urbanization varies across regions, suggesting that distinct policy interventions may be needed for different regional housing markets.